Time and risk diversification in real estate investements: Assessing the ex post economic value - Carolina Fugazza; Massimo Guidolin; Giovanna Nicodano (The University of Manchester, Manchester Business School, 2009)
Welfare gains to long-horizon investors may derive from time diversification that exploits non-zero intemporal return correlations associated with predictable returns. Real estate may thus become more desirable if its returns are negatively serially correlated. While it could be important for long horizon investors, time diversification has been mostly investigated in asset menus without real estate and focusing on in-sample experiments. This paper evaluates ex post, out-of-sample gains from diversification when E-REITs belong to the investment opportunity set. We find that diversification into REITs increases both the Sharpe ratio and the certainty equivalent of wealth for all investment horizons and for both Classical and Bayesian (who account for parameter uncertainty) investors. The increases in Sharpe ratios are often statistically significant. However the out-of-sample average Sharpe ratio and realized expected utility of long-horizon portfolios are frequently lower than that of a one-period portfolio, which casts doubts on the value of time diversification.
Keywords: 330; real time asset allocation; real estate; ex post performance; predictability; parameter uncertainty; Immobilienfonds; Portfolio-Management; Rendite; Zeitverwendung; USA